2012
DOI: 10.1021/es302779b
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Chironomids in Metal Polluted Andean High Altitude Streams: Does Melanin Play a Role?

Abstract: In high altitude Andean streams an intense solar radiation and coinciding metal pollution allow the persistence of only a few specialized taxa, including chironomids. The aim of the present study was therefore to determine the mechanisms underlying the persistence of chironomids under these multiple stress conditions, hypothesizing that melanin counteracts both the adverse effects of solar radiation and of metals. Melanin was determined in chironomids from reference and metal polluted streams at 3000 and 4000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…However, pigmentation in these species is not known to be plastic. Since G. maculosus can self-fertilize, the capacity of an individual to express either black or brown phenotype in response to differential UV exposure may have been selected over non-plastic melanic morphs, which are known to occur as adaptations to altitudinal gradients in UV intensity in some lizards [12] and insects [5759]. Skin colour in G. maculosus most likely plays a photoprotective role, leading to incidental camouflage against the different substrate types of each habitat.…”
Section: Discussionmentioning
confidence: 99%
“…However, pigmentation in these species is not known to be plastic. Since G. maculosus can self-fertilize, the capacity of an individual to express either black or brown phenotype in response to differential UV exposure may have been selected over non-plastic melanic morphs, which are known to occur as adaptations to altitudinal gradients in UV intensity in some lizards [12] and insects [5759]. Skin colour in G. maculosus most likely plays a photoprotective role, leading to incidental camouflage against the different substrate types of each habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of only one species in metal-rich streams may indicate a strong reduction in genetic variability, as previously described for populations of invertebrates inhabiting sites heavily contaminated by metals (van Straalen & Timmermans, 2002;Fratini et al, 2008;Ungherese et al, 2010). Recently, it was observed that chironomids from higher altitudes and from metalrich sites in the Andes contained more melanin than species from reference and from lower sites, which suggests that melanin may function both as a UV-B radiation protector and metal chelator (Loayza-Muro et al, 2013). Physiological adjustments may be responsible for such tolerance, since Chironomus species from contaminated sites are better able to regulate their body concentrations of metals than other taxa (Krantzberg & Stokes, 1989).…”
Section: Discussionmentioning
confidence: 62%
“…Physiological adjustments may be responsible for such tolerance, since Chironomus species from contaminated sites are better able to regulate their body concentrations of metals than other taxa (Krantzberg & Stokes, 1989). Allocation of energy towards tolerance mechanisms, such as metal-binding metallothioneins (Gillis, Reynoldson & Dixon, 2006), melanin production or cuticle sclerotisation in chironomids (Loayza-Muro et al, 2013), may enforce a trade-off evidenced in a reduced growth (Sibly & Calow, 1989). Genetic adaptation has also been considered as a general mechanism of metal tolerance in insects from heavily polluted environments, including Chironomus species (Groenendijk et al, 2002;van Straalen & Timmermans, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the high Andes (>3000 m), UV-B radiation presents a strong temporal and spatial variation, increasing with altitude and being particularly intense during the summer, when radiation peaks and reduced cloudiness and shallow water leave benthic communities more exposed to solar radiation (Cabrera, Bozzo & Fuenzalida, 1995;Zaratti, 2003;Loayza-Muro et al, 2013). Given these strong UV-B gradients, we hypothesised that pigment concentration in macroinvertebrates may be an adaptive response to particularly high UV-B radiation, especially during the dry season at the highest altitude sites.…”
Section: Introductionmentioning
confidence: 99%